Reducing Violence Risk? Some Positive Recidivism Outcomes for Canadian Treated High-Risk Offenders - Higgs, Tamsin (Criminal justice and behavior, 2019)
In pursuit of “what works” in violent offending behavior programs, there remain insufficient evaluations of program outcomes. Three hundred forty-five offenders from the Canadian Violence Prevention Program (VPP) were compared after an average 3-year follow-up with 338 non-VPP participants. Outcomes measured were new convictions for violent, sexual, or general offenses. Intent-to-treat design was used. Subsequently, participants who completed or did not complete the program were compared with the non-VPP group. Further analyses considered Indigenous and non-Indigenous subgroups. Overall, lower recidivism rates were associated with VPP completion, both in the complete sample and ethnic subgroups. However, the main finding of significantly lower likelihood of violent recidivism was found only for the Indigenous offenders, while significantly lower likelihood of general (nonviolent) recidivism was specific to non-Indigenous offenders. Results are interpreted cautiously in relation to program effectiveness given the quasi-experimental design and the important implications of outcome studies for correctional services.